Comments at the Third Multi-Stakeholder Platform Meeting of the Global Agenda of Action in Support of Sustainable Livestock Sector Development - Steinfeld, H. (International Livestock Research Institute, 2013)
Henning Steinfeld leads the livestock sector analysis and policy branch at the Food and Agriculture Organization of the UN. He spoke at the sidelines of the Third Multi-Stakeholder Platform Meeting of the Global Agenda of Action in Support of Sustainable Livestock Sector Development co-hosted in Nairobi, Kenya by ILRI, FAO and AU-IBAR, 22-24 January 2013.